Developing Winter Food Barley for the Pacific Northwest of the US. Issue 4 (1st July 2015) - Meints, Brigid; Cuesta‐Marcos, Alfonso; Ross, Andrew S.; Fisk, Scott; Kongraksawech, Teepakorn; Marshall, Juliet M.; Murphy, Kevin; Hayes, Patrick M.
ABSTRACT: Barley ( Hordeum vulgare L.) has been cultivated for human consumption for millennia. However, most North Americans do not regularly consume barley as a foodstuff. In the last decade, there has been renewed interest in barley production for human consumption. A number of quality traits are used to estimate nutritional value and are useful for food processing. These include β‐glucan, grain protein, kernel hardness, solvent retention capacity (SRC), and hull type. The Pacific Northwest (PNW) of the US is a high‐yielding region that has a reputation for setting dietary and nutritional trends. However, there are currently no winter food barleys adapted to this area. To determine the potential suitability of winter growth habits for food barley production in the PNW, we developed and tested 14 advanced lines. The germplasm was developed via marker‐assisted and phenotypic selection and included hulled lines with waxy starch and hull‐less lines with normal starch. Agronomic and food quality traits were measured on samples from three representative environments (dryland, irrigated, and high rainfall) over a 2‐yr period allowing for assessment of performance within and across locations, as well as genotype × environment interaction. Lines with waxy starch had significantly higher levels of β‐glucan, harder kernels, and higher water retention capacity. Hull‐less lines had, on average, slightly lower yields than hulled lines, with an average difference of 105 kg ha −1 . Our future food barley variety development will focus exclusively on hull‐less types because of the simplified processing and consumer interest in the nutritional benefits of whole grain.